THE IMPLEMENTATION OF MANAGEMENT INFORMATION SYSTEMS IN THE DIGITAL ERA: CHALLENGES AND SOLUTIONS - Ana Nurfadilah; Ilham (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) - Institut Teknologi dan Bisnis Semarang, 2024)
This research discusses the challenges and solutions of implementing management information systems in the digital era. In the digital era, the development of information technology is rapidly advancing and has brought significant changes to various aspects of life, including the business world. Companies and organizations are now required to be more responsive, faster, and more efficient in their operations. One way to achieve that goal is through the implementation of a Management Information System. (SIM ). This research uses the literature review method by examining the implementation of SIM through previous studies and articles. The results of this study indicate that the implementation of SIM does not always go smoothly; there are challenges that must be faced, such as costs, the integration of old systems into new ones, and data security. Therefore, solutions are needed to address these challenges.